The presence of Philadelphia chromosome does not confer poor prognosis in adult pre‐B acute lymphoblastic leukaemia in the tyrosine kinase inhibitor era – a surveillance, epidemiology, and end results database analysis. (18th October 2017) - Igwe, Igwe J.; Yang, Dongyun; Merchant, Akil; Merin, Noah; Yaghmour, George; Kelly, Kevin; Ramsingh, Giridharan
Summary: The BCR‐ABL1 fusion gene is caused by a translocation between chromosomes 9 and 22, resulting in an abnormal chromosome 22 (Philadelphia chromosome; Ph). Prior to the introduction of tyrosine kinase inhibitors (TKI), the presence of BCR‐ABL1 conferred a poor prognosis in patients with acute lymphoblastic leukaemia (ALL). We compared the survival of Ph+ and Ph−ALL during the period when TKIs were universally available in the US for Ph+ALL, using a Surveillance, Epidemiology, and End Results (SEER) Database analysis. A total of 2694 patients with pre‐B ALL (206 Ph+ALL; 2488 Ph−ALL) aged ≥18 years, who were diagnosed between 2010 and 2014, were identified in SEER registries. The median overall survival (OS) was 32 months in Ph+ALL (95% confidence interval [CI] 18 months‐not reached) and 27 months (95% CI 24–30 months) in Ph−ALL (Log‐rank test P ‐value 0·34). Older age was associated with worse prognosis in both Ph+ALL and Ph−ALL. Age‐adjusted OS was inferior in Hispanics and African‐Americans compared to non‐Hispanic whites. Survival of pre‐B ALL shows continued improvement with time. Philadelphia chromosome status does not confer poor prognosis in pre‐B ALL in the TKI era: prognostic factors in pre‐B ALL should be re‐evaluated in the light of this finding.